Sec-Health : A Block Chain-Based Protocol for Securing Health Records - Renikunta, Harini; Padakanti, Priyanka; Palakurla Vasantha; Madde Kumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Storing and participating health records through electronic systems pose security pitfalls. To address them, several countries’ regulations have established that healthcare information systems must fulfill security parcels (confidentiality, access control, integrity, cancellation and obscurity) and reciprocal bones (exigency access and interoperability). Upon diving these issues, several proffers present security limitations and/ or specific only. We propose Sec- Health, a block chain- grounded protocol that secures health records, addressing all of the main security and reciprocal parcels defined in current regulations. We show that Sec- Health is a suitable result by assaying it under several attack scripts and describing how it overcomes the problems of being results. likewise, we estimate a Sec- Health evidence of Concept, showing that it can reduce the time to pierce health records, and reduce customer- side outflow, compared to affiliated work.